2021
DOI: 10.1525/mp.2021.38.5.456
|View full text |Cite
|
Sign up to set email alerts
|

Singing in the Brain

Abstract: Music that gets “stuck” in the head is commonly conceptualized as an intrusive “thought”; however, we argue that this experience is better characterized as automatic mental singing without an accompanying sense of agency. In two experiments, a dual-task paradigm was employed, in which participants undertook a phonological task once while hearing music, and then again in silence following its presentation. We predicted that the music would be maintained in working memory, interfering with the task. Experiment 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 54 publications
3
23
0
Order By: Relevance
“…This task was chosen because it provides continuous movement which may be in synchrony without being rhythmic, as we were concerned that a strongly rhythmic stimulus may encourage participants to entrain their responses to the stimulus (Killingly et al, 2021), thus influencing reaction times and confounding the results. The animated Gabor patch provides a solution, as it has a continuous movement without providing a "beat" that participants could tap in time with.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This task was chosen because it provides continuous movement which may be in synchrony without being rhythmic, as we were concerned that a strongly rhythmic stimulus may encourage participants to entrain their responses to the stimulus (Killingly et al, 2021), thus influencing reaction times and confounding the results. The animated Gabor patch provides a solution, as it has a continuous movement without providing a "beat" that participants could tap in time with.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants were not required to move or tap in time with anything, only to respond by categorising stimuli. This makes it difficult to compare to previous work, like that of Hove and Risen (2009), but it did remove potential confounds that could arise from measuring reaction times while participants perform rhythmic actions (Killingly et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, I argue that what makes earworms distinct from other aspects of auditory cogni-tion…is the reaction of people experiencing an earworm. Beaman's implication that it is solely the visceral negative reaction that makes the earworm phenomenon distinct is not consistent with the majority of literature that has generally shown that, for most people, experiencing an earworm is not unpleasant or disturbing (most of the time) (Halpern and Bartlett 2011;Killingly et al 2021; Williamson and Jilka 2014). The alternative explanation by Beaman is that if one is not voluntarily suppressing the earworm then one is instead voluntarily "singing along"-either of which (suppression or singing)-could cue repetition.…”
Section: Introductionmentioning
confidence: 91%
“…This challenge was highlighted in our previous work (Killingly et al, 2021), where it was evident that factors such as the enjoyment of a song and desire to sing along were also associated with previous exposure to the music (in terms of participants' perceived familiarity). While songs tended to vary in terms of how familiar people were with them, there were consistent significant relationships among participants' ratings of their enjoyment, familiarity with, and desire to sing along to different songs, and self-reported earworms, indicating that higher levels of familiarity were positively associated with higher levels of enjoyment and the desire to sing along.…”
mentioning
confidence: 93%